Copper-Catalyzed Alkenylation of Alcohols with β-Nitrostyrenes via a Radical Addition–Elimination Process - Guo, Sheng-rong; Yuan, Yan-qin (Synlett, 2015)
A new method for the preparation of allylic alcohol derivatives has been developed via a radical mechanism using DTBP as the radical initiator promoted by copper salt. The C(sp3)–H bond in various alcohols, toluene derivatives, and alkanes were successfully converted into C–C bonds to yield the desired products in moderate to good yields.
Keywords: (E)-β-nitrostyrenes; alkenylation; alcohols; free-radical; C(sp3)–H bonds